2009
DOI: 10.1038/ejhg.2009.179
|View full text |Cite
|
Sign up to set email alerts
|

Gain-of-function variant in GLUD2 glutamate dehydrogenase modifies Parkinson's disease onset

Abstract: Parkinson's disease (PD), a common neurodegenerative disorder characterized by progressive loss of dopaminergic neurons and their terminations in the basal ganglia, is thought to be related to genetic and environmental factors. Although the pathophysiology of PD neurodegeneration remains unclear, protein misfolding, mitochondrial abnormalities, glutamate dysfunction and/or oxidative stress have been implicated. In this study, we report that a rare T1492G variant in GLUD2, an X-linked gene encoding a glutamate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 37 publications
1
57
0
Order By: Relevance
“…In hemizygous male subjects, it has been speculated that this might be due to enhanced glutamate oxidative phosphorylation in dopaminergic neurons. It is noteworthy that there was no association in heterozygous female patients with PD, which was attributable to the finding that estrogens suppress enzyme activity (Plaitakis et al, 2010).…”
Section: Sex-specific Estrogen Actions In the Brainmentioning
confidence: 96%
“…In hemizygous male subjects, it has been speculated that this might be due to enhanced glutamate oxidative phosphorylation in dopaminergic neurons. It is noteworthy that there was no association in heterozygous female patients with PD, which was attributable to the finding that estrogens suppress enzyme activity (Plaitakis et al, 2010).…”
Section: Sex-specific Estrogen Actions In the Brainmentioning
confidence: 96%
“…These observations, taken together with recent findings showing that overexpression of GDH1 in mice results in age-dependent degenerative changes in the CA1 region of the hippocampus (34), suggest that a tight regulation of GDH activity is of importance for nerve tissue function and degeneration. Regarding deregulation of hGDH2 in human disorders, recent studies revealed that patients with Parkinson disease, who were hemizygous for T1492G polymorphism in the GLUD2 gene, experienced onset of their disease 8 -13 years earlier than patients with other genotypes in two populations of diverse genetic background (35). However, female Parkinson disease patients who were heterozygous for this allele were protected.…”
Section: Discussionmentioning
confidence: 98%
“…However, female Parkinson disease patients who were heterozygous for this allele were protected. The T1492G polymorphism is within the coding region of the GLUD2 gene and results in the substitution of Ala for Ser 445 in the regulatory domain of hGDH2 (35). The S445A variant, obtained in recombinant form by expressing the T1492G-GLUD2 cDNA in Sf21 cells, displayed enhanced basal activity that was sensitive to inhibition by estrogens (35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations